Profile and Antibiotic Susceptibility Pattern of Bacterial Isolates from Mobile Phones of Healthcare Workers in a Tertiary Care Centre of Nepal - Sapkota, Jyotshna; Jha, Beena; Mishra, Bhavesh; Shrestha, Deepti; Barakoti, Achut; Sharma, Manisha (Journal of Institute of Medicine Nepal, 2020)
Introduction Nosocomial infection is a serious problem worldwide. Healthcare workers mobile phones may act as vehicle for nosocomial infections. Mobile phones are rarely cleaned and healthcare workers frequently use them thorough out their time in hospitals. The objective of this study is to determine the rate of contamination of mobile phones, prevalent microorganisms and their antibiotic sensitivity pattern. Methods The descriptive cross-sectional study was carried out in Clinical Microbiology laboratory from July 2019 to September 2019 after ethical approval. Samples were collected aseptically by rolling sterile swabs over the exposed surfaces of the mobile phones and inoculated on the agar plates and incubated aerobically. After incubation, plates were examined for growth. Bacteria were identified by standard microbiological procedure and antibiotic sensitivity test of isolated pathogens was done using Muller Hinton Agar by Kirby-Bauer method. Statistical analysis was done by Excel 2018. Results Of the 198 mobile phones sample cultures, 112 (56.6%) samples showed 7 different types of bacteria. Mixed growth was observed in 3 mobile phones and total of 115 bacterial isolates were identified. Staphylococcus species (74.7%) were predominant organism followed by Acinetobacter spp, Klebsiella pneumoniae, E. coli, Citrobacter and Pseudomonas aeruginosa. Total 37.5% of Staphylococcus aureus were methicillin-resistant Staphylococcus aureus (MRSA). Conclusion Mobile phones may have potential pathogenic microorganisms on their surface and can act as vector in spread of infectious agents in hospital settings. It is recommended to disinfect mobile phones regularly and to implement hand washing practices and regulations around the use of mobile phones in hospital settings.